The potential of methane production using aged landfill waste in developing countries: A case of study in Colombia. Issue 1 (1st January 2019) - Caicedo-Concha, Diana M.; Sandoval-Cobo, John J.; Fernando, Colmenares-Quintero Ramón; Marmolejo-Rebellón, Luis F.; Torres-Lozada, Patricia; Sonia, Heaven
Abstract: In the current context of climate change and global energy demand, the use of energy from waste has become one strategy for the reduction of greenhouse gas (GHG) emissions and the replacement of fossil fuels by other non-conventional energy sources through the use of biogas produced in landfills. Although there have been some improvements in solid waste management practices in Colombia, current levels of recycling and materials recovery are still poor as only about 10% of the waste produced is recovered, so it is expected that, as for most developing countries, final disposal in landfills will continue to be the main form of municipal solid waste (MSW) management in the coming decades. The optimization of waste degradation and stabilization processes is an essential key aspect for the environmental performance and economic sustainability of waste management systems in developing countries like Colombia. However, assessing the feasibility of biogas production in landfills requires a reasonable level of accuracy for the generation of methane, a sufficient understanding of the underlying generation processes and their relation with the physicochemical characteristics of the waste and landfill disposal conditions. Source segregation of MSW is either poor or non-existing in Colombia, as in most developing countries, which makes difficult to predict landfill gas generation even with the aid of current landfill emissions models. Only a few studies have been conducted to characterize biogas and methane production potential of mixed MSW landfilled in Latin-American countries, with few studies reported in Brazil and in Colombia. In this study, we show the results of biochemical methane potential (BMP) tests with 4–5 years old samples of municipal solid waste (MSW) excavated from a landfill site located in Colombia. Collected samples were characterized and the easy and medium biodegradable fractions used in the experiments. The results show an average total production of 34.8 − 37.9 L CH4 kg-1 DM added which is comparable with similar studies using excavated landfilled waste of similar characteristics. These results suggest that considering the potential of methane production from landfilled waste in developing countries, it is an alternative that could be considered to enhance the environmental performance of landfill sites by reduction of the emissions of uncontrolled CH4 and promote the use of non-conventional energy sources.